The most wonderful crime of the year : a novel - Carter, Ally (Avon, an imprint of HarperCollinsPublishers, 2024)
"Meet Maggie Chase and Ethan Wyatt.She's the new queen of the cozy mystery. He's Mr. Big-Time thriller guy. But when they both accept a cryptic invitation to attend a Christmas house party at the English estate of a reclusive fan, neither is expecting their host to be the most powerful author in the world...That night, the weather turns, and the next morning Eleanor is gone. She vanished from a locked room, and Maggie has to wonder: Is Eleanor in danger? Or is it all some kind of test? Is Ethan the competition? Or is he the only person in that snowbound mansion she can trust?"--